Effects of different types of nitrogen fertilizers on grain yield and nitrogen utilization of double -cropping rice in yellow clayey soil - LIU Yanling; LAI Qing; XU Hanzeng; ZHANG Xuan; WU Lianghuan; GU Yan; HE Yan; KONG Xiangjun (浙江大学学报. 农业与生命科学版, 2013)
Yellow clayey soil is one type of medium-low yield farmland, while rational applications of nitrogen fertilizer have great significance for enhancing its grain yield. Using controlled-release fertilizer as basal nitrogen fertilizer, single basal application is an effective way to improve the labor productivity, reduce fertilizing costs, increase farmer income, and also increase the yield and nitrogen use efficiency. However, its fertilizer efficiency is more affected by environment. Therefore, this study aims to look for suitable types and contents of nitrogen fertilizer for the double-cropping rice in yellow clayey soil in Jinqu Basin, and to provide theoretical basis for reforming medium-low yield paddy soil.A field experiment was conducted to study the effects of no nitrogen fertilizer (CK), conventional fertilizer (prilled urea (PU) application of many times) and different types of controlled-release fertilizer as basal nitrogen fertilizer to single basal application on yield, dry matter and Naccumulation, post-anthesis dry matter amount and nitrogen utilization of double-cropping rice in yellow clayey soil. The equal amount of nitrogen (N) application with 180 kg/hm2 was used for each fertilizer treatment.The results showed that, compared with CK, nitrogen treatments significantly increased grain yield by 77.7% 103.5% on early rice and 56.4% 72.9% on late rice, with the profit increased by 7 149 10 648 Chinese Yuan/hm2 and 8 055 10 950 Chinese Yuan/hm2 respectively. Compared with convention fertilizer (PU 100%), all treatments of controlled-release fertilizers as basal nitrogen fertilizer to single basal application had different performance on early and late rice. The grain yield, profit and agronomic nitrogen use efficiency (ANUE) were significantly increased by more than 9.9%, 2 281 Chinese Yuan/hm2, 3.7 kg/kg, respectively, in the treatments of urea-formaldehyde (UF 100%) and urea with nitrapyrin (NPU 100%) on early rice, NPU 100% and 70% sulfur-polyester resin-coated urea (SPCU) mixing 30% prilled urea (SPCU 70% +PU 30%) on late rice. The treatment of NPU 100% also significantly increased nitrogen use efficiency (NUE) by 27.3% and 78.3% respectively on early and late rice.In conclusion, under this field experiment conditions, the modes of nitrogen application in the treatments of UF 100% or NPU 100% on early rice, NPU 100% or SPCU 70% +PU 30% on late rice can meet the demand of rice growth when the yield, economic efficiency and nitrogen use efficiency are taken into account. Importantly, the application of NPU showed similar nutritional contribution and economic efficiency on the early and late rice, and should be taken as an available and economic nitrogen fertilizer on double-cropping rice in yellow clayey soil.